Adaptive mechanisms in no flow vs. low flow ischemia in equine jejunum epithelium: Different paths to the same destination - Dengler, Franziska; Sternberg, Felix; Grages, Marei; Kästner, Sabine BR; Verhaar, Nicole (Frontiers in Veterinary Science, 2022)
Intestinal ischemia reperfusion injury (IRI) is a frequent complication of equine colic. Several mechanisms may be involved in adaptation of the intestinal epithelium to IRI and might infer therapeutic potential, including hypoxia-inducible factor (HIF) 1α, AMP-activated protein kinase (AMPK), nuclear factor-erythroid 2-related factor 2 (NRF2) and induction of autophagy. However, the mechanisms supporting adaptation and thus cellular survival are not completely understood yet. We investigated the activation of specific adaptation mechanisms in both no and low flow ischemia and reperfusion simulated in equine jejunum epithelium in vivo. We found an activation of HIF1α in no and low flow ischemia as indicated by increased levels of HIF1α target genes and phosphorylation of AMPKα tended to increase during ischemia. Furthermore, the protein expression of the autophagy marker LC3B in combination with decreased expression of nuclear-encoded mitochondrial genes indicates an increased rate of mitophagy in equine intestinal IRI, possibly preventing damage by mitochondria-derived reactive oxygen species (ROS). Interestingly, ROS levels were increased only shortly after the onset of low flow ischemia, which may be explained by an increased antioxidative defense, although NFR2 was not activated in this setup. In conclusion, we could demonstrate that a variety of adaptation mechanisms manipulating different aspects of cellular homeostasis are activated in IRI irrespective of the ischemia model, and that mitophagy might be an important factor for epithelial survival following small intestinal ischemia in horses that should be investigated further.